Impact of oral isotretinoin therapy on musculoskeletal system and physical activity in patients with acne - Małgorzata Drozd; Jakub Czarnota; Michał Dobrzyński; Tomasz Skubel; Dorota Sokół; Iga Dudek; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Introduction and purpose: Isotretinoin, the vitamin A derivative, has been commonly used in treatment of acne vulgaris for years. Despite its unquestionable efficacy, chronic oral isotretinoin treatment leads to multiple side effects. The aim of study is analysis of musculoskeletal symptoms prevalence during oral isotretinoin treatment and their impact on physical activity. Material and methods: The study was conducted using the original survey questionnaire shared online among members of Polish group of patients treated for acne. Total of 196 responses were analyzed and compared with up-to-date literature related to the topic. Results: 86,7% of respondents reported at least one of the musculoskeletal symptoms. The most common were back pain (82,7%), fatigue and lethargy (70,4%), myalgia (55,1%) and arthalgia (32,1%). In 97,6% cases adverse effects were developed within the first 6 months of treatment. In 64,2% they persisted during the whole therapy, sometimes even beyond. Due to musculoskeletal side effects, in 2,4% cases dose reduction was necessary, 1,8% of respondents had to stop treatment and 48% had to limit or stop physical activity. 71,4% of repondents reported that lower back pain occurred or escalated during isotretinoin treatment. Conclusions: Prevalence of reported musculoskeletal symptoms is very high and totals 86,7%. They result in prolonged limiting or stopping of physical activity in almost 50% of people. Although musculoskeletal symptoms are typically benign, possibility of severe disorders and potential permanent effects must be taken into consideration.